An Improved Process for the Preparation of the p-tert-butylcalix[4]arene: from Laboratory-scale Synthesis to Scale-up Development - A. A. Fat'yanova; A. S. Gusak; O. A. Trofimova; P. E. Prokhorova (Chimica Techno Acta, 2016)
The article describes the synthesis of p-tert-butylcalix[4]arene with different downloads of the starting compounds. The obtained data revealed the dependence of the yield on solvent, time and download amount. The description of technological process and material flows are given in this article.